2020
DOI: 10.9734/ijtdh/2020/v41i1230336
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Utilization of School Health Services among Senior Secondary School Students in Egor Local Government Area, Benin City, Edo State

Abstract: Background: The knowledge of school health services among all students in various schools are essential in ensuring that students are equipped with the expected benefits and right attitude of utilizing the services. Aim: The aim of this study was to assess knowledge, attitude and utilization of school health services among senior secondary school students in Egor local government area, Edo State. Methods: Using a multistage sampling two secondary schools were selected from the thirteen public secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…This contradicts the results of the research, which indicated a high understanding of the components of school health services in both types of schools. The study conducted by Osian et al (2020) revealed that a majority of the respondents (57.6%) possessed a high level of knowledge regarding school health services. Additionally, 30.5% had a moderate level of knowledge, while 11% had a poor level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This contradicts the results of the research, which indicated a high understanding of the components of school health services in both types of schools. The study conducted by Osian et al (2020) revealed that a majority of the respondents (57.6%) possessed a high level of knowledge regarding school health services. Additionally, 30.5% had a moderate level of knowledge, while 11% had a poor level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…To promote children's well-being, avoid illnesses, and address any health issues that might have immediate or long-lasting effects, it is crucial to consider that children at this stage are still undergoing physical and mental growth and development. (Osian, et al 2020). Like other settings, schools subject children to many hazards such as diseases, accidents, and mental and physical strain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations